Pengaruh Risk Attitude, Risk Perception, dan Subjective Norm terhadap Risk Intended Behavior dari Restoran Makanan yang Tidak Memiliki Sertifikasi Halal bagi Konsumen Muslim, dengan Variabel Moderator Religiusitas - Winahyu, Rojib Burhan (BISMA (Bisnis dan Manajemen), 2018)
Restaurant in East Java last few years has increased significantly, where they come to offer a wide selection of new and exciting menus to satisfy consumers. On the other hand a lot of publicity to grow, both through print and electronic media about the composition of the food in them contain components harmful to the health of the body as well , including the types of food that is prohibited for consumption by religious law ( especially for Muslims ) widely circulated and highly troubling . This phenomenon is reinforced with only three restaurants in East Java that has a halal certification. Of course it is ironic that the majority of the population in East Java is Muslim. It should be noted by the company restaurant food is how consumer behavior in the face of such phenomena. Where the risk is influenced consumer behavior from attitudes towards risk (risk attitude), risk perception, subjective norms and consumer behavior in the face of possible risks that would happen (risk behavior intention) of restaurant that havent halal certification. This study using a quantitative design with statistical tools Partial Least Square (PLS). The results found that the risk attitude, risk perception, subjective norm effect on risk intention behavior. While the value of religiosity a person does not give effect to the relationship of risk attitude and risk perception on risk behavior intention